Exploring new dimensions of urban governance: The development of administrative systems in Trieste and Fiume (Rijeka) during the final decades of the Habsburg Empire (1850–1918) - Bálint Hilbert (Hungarian Geographical Bulletin)
Urban governance is often perceived as a concept that has emerged over the past half-century, evolving from the policy of urban government. The analysis of this shift, known as the “transformation thesis,” has been criticized by recent studies in the field, which focus on the theory of metagovernance. However, both branches of urban governance literature heavily rely on knowledge of American cities, hindering a comprehensive understanding of the phenomenon. There is a growing demand to broaden the temporal and geographical scope of case studies and conduct more comparative research to better understand the roots and current processes of urban governance. While the fundamental driving forces behind the emergence of modern municipal administration during the 19th century have been adequately explored, various characteristics of different geographical locations might add new dimensions and approaches to understanding urban governance. This study offers a comprehensive insight into the birth and early formation of urban governance systems in the free ports of the Austro-Hungarian Monarchy, namely Trieste and Fiume (Rijeka in Croatian). By analyzing legal documents and applying a mixed-method approach, this study unravels the institutional structures, electoral systems, and municipal authorities of Trieste and Fiume from the 1848 Revolution until the end of the First World War. In addition to the historical and Central European perspectives, this paper aims to explore rarely considered contextual factors of urban governance, such as legal-administrative, socio-economic, and political elements. The comparative analysis of Trieste and Fiume demonstrates that even within the same empire, a wide range of diverse influences could shape urban governance systems. Despite these varied factors and significantly different administrative contexts, surprisingly similar governance practices could also emerge.